Analysis of the Problem-Based Story Model Development with ICT Kahoot and the Effectiveness on Students’ Metacognition Awareness and Science Process Skills - Widiet Nurcahyo Ramadhana; Suratno Suratno; Yushardi Yushardi (Eduvest - Journal of Universal Studies, 2022)
This study aims to develop a problem-based story learning model with ICT using the Kahoot interactive quiz that could increase students' metacognition awareness and science process skills which were determined by the validity, practicality, and effectiveness of the learning model. This research was a research development (R&D) 4D Thiagarajan through four stages such as define, design, develop, disseminate. The effectiveness of data collection was done by giving pre-test and post-test questions on metacognition awareness using MAI (Metacognition Awareness Inventory) and questions on students' science process skills by looking at the increase in the average score of normalized gain. The results showed that the learning model was effective for increasing awareness of metacognition, this was based on the average N-Gain in the small group test, large group test, and the dissemination test with an average of 0.62 in the medium category, and on the students' science process skills with an average N-Gain value of 0.61 in the medium category. This model was also declared “valid” by the expert validators and users which was supported by empirical validation results. The practicality of implementing the PBS model had also been tested by observing the teacher's ability in classroom learning, learning responses to the ease with which teachers used the model, and student responses to the learning model applied by the teacher. The final result showed that the problem-based storytelling model developed had met the valid, effective, and practical criteria.